Analisa pemanfaatan sumber daya alam perikanan tangkap di provinsi Sulawesi Barat - Sutisna, Muhammad Aziz Rizal (Journal of Earth Kingdom, 2024)
The utilization of capture fisheries resources in West Sulawesi Province is currently at its lowest level compared to five other provinces in the Sulawesi region, although overall utilization conditions have reached fully exploited and over-exploited status. The low utilization is caused by the lack of fishing facilities and infrastructure as well as the lack of empowerment of fishermen in the province. This study aims to analyze the level of utilization of capture fisheries resources and the factors influencing them in West Sulawesi Province. The data collection method used was a survey and interviews with 50 fishermen in 5 districts/cities. The results show that the average productivity of fishermen's fishing is still very low compared to other provinces in Sulawesi. In addition to the lack of capital and infrastructure, the low level of education and skills of fishermen is also a major cause. Therefore, various efforts are needed to empower fishermen through training and capital assistance so that the utilization of capture fisheries resources can be optimal and sustainable.